Certification and preservation of artworks in digital environments - Damiani, Concetta (JLIS.it, 2022)
Reflecting about the documentary heritage of artists requires the consideration of archival, legal, historical-artistic and museological factors. If the analogue productions of artifacts and the correlated documentation have been studied, transferring the creative perspective into a digital environment asks to face a reality in turmoil: the ways of expressing and representing contemporary art, in balance between digital and crypto art, require new visions in the production and management of works. In this redefinition of roles and relationships, which almost exclusively concern the documentary structure and the technological and digital components, document systems assume a primary role.